A cleanser based on sodium laureth carboxylate and alkyl carboxylates washes facial sebum well but does not induce dry skin. (December 2014) - Yokoi, Aya; Endo, Koji; Ozawa, Toshiaki; Miyaki, Masahiro; Matsuo, Keiko; Nozawa, Kazumi; Manabe, Motomu; Takagi, Yutaka
Summary Background Because excess sebum and/or metabolites of sebum induce skin problems, cleansers that can remove those kinds of sebum are sought after. However, many people, especially who have little facial sebum, are afraid to wash off sebum well because that may induce dry skin. This concern may be caused by the result that cleansers with a high cleansing ability tend to decrease not only facial sebum but also natural moisturizing factors and intercellular lipids that are essential for cutaneous function. Recently, we have developed a new cleanser based on sodium laureth carboxylate and alkyl carboxylates (AEC/soap) that cleans sebum well without penetrating the stratum corneum. Objectives This trial was aim to clarify the effects of sebum removal by AEC/soap‐based cleanser on the induction of dry skin. Methods We designed a controlled single blind parallel trial. Thirty female subjects with mild dry skin were assigned randomly to two groups: one group used AEC/soap‐based cleanser while the other group kept using their usual facial cleanser twice a day for 4 weeks in the winter season. Results Using a colored artificial sebum mixture, it was demonstrated that this cleanser washed sebum well. Following usage of this cleanser, their dry skin improved rather than worsen which was indicated by instrumental analysis and visual assessment. These improvements were recognized by subjects. Conclusions These results suggest that AEC/soap‐based cleanser washes off facial sebum well, but it has little effect on the induction of dry skin because of less penetration into stratum corneum.